Diversity of food plants found in backyards of the Bom Lugar community, Campo Maior-PI (Research, Society and Development, 2021)
Backyards are places close to homes, easily accessible to residents and play an important role in promoting nutritional and food security for families around the world, as well as in the conservation of biodiversity. The objective was to carry out a survey of food plants grown in rural backyards in the community of Bom Lugar, in the municipality of Campo Maior / PI. The data were collected through 54 semi-structured interviews with the application of forms and a guided tour with the backyard keepers. For data analysis, descriptive statistics and the Shannon Diversity Index (H’) were used. Among the interviewees, most were female (82.1%), married (69.6%) and with incomplete primary education (64.2%). 70 species of food use were identified. Solanaceae, Anacardiaceae, Annonaceae, Mythaceae and Rutaceae were the most representative families in number of species. The species Anacardium occidentale L. was highlighted in backyards due to its high economic value, as well as Manihot esculenta Crantz. Shannon's Diversity Index was (H') = 3.703. Most of the plants found cultivated were fruitful, followed by vegetables and condiment species. Exotic plants stood out compared to native plants. Bom Lugar's backyards are a source of nutrients and income for residents, thus ensuring subsistence and food security.